2019
DOI: 10.1111/epi.14661
|View full text |Cite
|
Sign up to set email alerts
|

Development of information sharing in language neocortex in childhood‐onset drug‐resistant epilepsy

Abstract: Summary Objective We studied age‐related dynamics of information sharing among cortical language regions with electrocorticographic high‐gamma modulation during picture‐naming and story‐listening tasks. Methods Seventeen epilepsy patients aged 4‐19 years, undergoing extraoperative monitoring with left‐hemispheric subdural electrodes, were included. Mutual information (MI), a nondirectional measure of shared information, between 16 pairs of cortical regions of interest, was computed from trial‐averaged 70–150 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…By having the same starting set of images across all patients, eliminating pictures that the patient was unable to name, and recording under similar environment, we have tried to mitigate the effects of word usage, accuracy, and stimulus context. Response latency for picture naming is also influenced by literacy levels, and mutual information in HGM between parcel pairs is affected by IQ ( Reis et al, 2001 ; Arya et al, 2019c ). Therefore, we excluded patients with VCI < 70.…”
Section: Discussionmentioning
confidence: 99%
“…By having the same starting set of images across all patients, eliminating pictures that the patient was unable to name, and recording under similar environment, we have tried to mitigate the effects of word usage, accuracy, and stimulus context. Response latency for picture naming is also influenced by literacy levels, and mutual information in HGM between parcel pairs is affected by IQ ( Reis et al, 2001 ; Arya et al, 2019c ). Therefore, we excluded patients with VCI < 70.…”
Section: Discussionmentioning
confidence: 99%
“…For the differences in edges that are predictive of expressive vs. receptive scores, our Grad‐CAM analysis found that there were commonalities between edges associated with expressive and receptive scores: they both involved bilateral structures and had one common structure (left angular gyrus). Significant information sharing was also identified by language‐associated electrocorticography high‐gamma modulation “within” frontal and temporoparietal language cortices, and “between” classical language areas in the dominant hemisphere (i.e., Broca's and Wernicke's areas) (Arya et al, 2019), suggesting that expressive and receptive language functions may communicate and share neural activity across multiple language regions. Interestingly, our result provided neurobiological evidence on a spatial redundancy (Schomers, Garagnani, & Pulvermüller, 2017) determined by our dilated CNN + RN to be most predictive of expressive and receptive scores (e.g., left ANG).…”
Section: Discussionmentioning
confidence: 99%
“…While task-based functional connectivity, CCSR-based effective connectivity, and DWI-based structural connectivity have speci c strengths, each method has an inevitable limitation. Previous studies using Granger causality reported that cortical sites showing task-related highgamma augmentation during a shared time window could propagate neural activity between them 12,13,20,114 . However, Granger causality cannot consistently distinguish direct versus indirect connectivity.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Our 6D dynamic tractography approach integrates all three modalities into a single model and visualization, which revealed the white matter pathways supporting rapid neural propagations between sites engaged to speci c linguistic stages. We hypothesize that the dynamic trajectories observable via 6D tractography are more likely to be used for auditory naming if the remote areas connected are simultaneously engaged in the same linguistic stage 12,13,20,114 . Indeed, we found that early CCSRs were larger when the stimulus and recording sites showed high-gamma augmentation during the same linguistic stage.…”
Section: Methodological Considerationsmentioning
confidence: 99%